Kilka uwag o polskiej terminologii chemicznej 2. połowy XIX wieku - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The purpose of this article is to present a source that has so far remained unused in the historical research of the Polish chemical terminology of the second half of the 19th century – Słownik terminologii lekarskiej polskiej [English: Polish Medical Terminology Dictionary] of 1881. This dictionary is a result of the efforts which the Polish medical doctors undertook to organise the Polish medical terminology in the 19th century. It also contains chemical terms. What is important, the dictionary demonstrates a phase of competition between two terminology schools: the Cracow school and the Warsaw school, juxtaposing various terms (mainly in synonymic strings) proposed by these schools.